Respuesta :

Answer:

[tex]y-6=\frac{1}{3} (x+1)[/tex]

Step-by-step explanation:

The point-slope formula is [tex]y -y_{1} =m(x -x_{1})[/tex] where we substitute a point (x,y) for [tex](x_{1},y_{1})[/tex].  

We have m=[tex]\frac{1}{3}[/tex] and (-1, 6). We input m and [tex]x_{1} =-1\\y_{1}=6[/tex].

[tex]y-6=\frac{1}{3} (x-(-1))\\y-6=\frac{1}{3} (x+1)[/tex].

We can convert into the slop-intercept from by simplifying the parenthesis and solving for y.

[tex]y-6=\frac{1}{3} (x+1)\\y-6=\frac{1}{3}x +\frac{1}{3}\\y-6+6=\frac{1}{3}x +\frac{1}{3}+6\\\\y=\frac{1}{3}x +6\frac{1}{3}\\\\[/tex]